Property rights, women's empowerment, and intersectionality in Nepal - Theis, Sophie (International Food Policy Research Institute, 2017)
Presented by Sophie Theis (IFPRI), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.